PENERAPAN ASSOCIATION RULE PADA SISTEM REKOMENDASI PRODUK PROPERTI BERDASARKAN POLA INTERAKSI PENGGUNA - Kristovel Printo Nana; Lukman Junaedi (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The increasing need for property makes various property companies have to compete to promote the best property options. Information system facilities are one of the main reasons for prospective buyers to get property information that best suits their needs. Each customer has a unique pattern of needs that can be obtained from the search pattern of the information system. This study tries to provide the best property product recommendations using the association rule method. The association rule method itself is a data mining method that is used to provide product recommendations based on user search activity patterns while opening an information system. After the association rule method is applied, the system can provide recommendations for the three best products with an attractive and easy-to-use information system.